Face-to-Face Sharing with Strangers and Altruistic Punishment of Acquaintances for Strangers: Young Adolescents Exhibit Greater Altruism than Adults - Hao, Jian; Yang, Yue; Wang, Zhiwen (Frontiers in Psychology, 2016)
Young adolescents are generally considered to be self-absorbed. Studies indicate that they lack relevant general cognitive abilities, such as impulse control, that mature in early adulthood. However, their idealism may cause them to be more intolerant of unfair treatment to others and thus result in their engaging in more altruistic behavior. The present study aimed to clarify whether young adolescents are more altruistic than adults and thus indicate whether altruistic competence is domain-specific. One hundred twenty-two young adolescents and adults participated in a face-to-face, two-round, third-party punishment experiment. In each interaction group, a participant served as an allocator who could share money units with a stranger; another participant who knew the allocator could punish the acquaintance for the stranger. Participants reported their emotions after the first round, and at the end of the experiment, the participants justified their behavior in each round. The results indicated that the young adolescents both shared more and punished more than did the adults. Sharing was associated with a reference to fairness in the justifications, but altruistic punishment was associated with subsequent positive emotion. In sum, greater altruism in young adolescents compared to adults with mature cognitive abilities provides evidence of domain-specificity of altruistic competence. Moreover, sharing and altruistic punishment is related to specific cognitive and emotional mechanisms respectively.